Interfacial fracture initiation strength of micro-scale Si/Cu components with different geometries: Applicability of the fracture mechanics criterion. (15th May 2022) - Takahashi, Yoshimasa; Kishimoto, Kaname; Morii, Yusuke; Arai, Shigeo; Higuchi, Kimitaka; Muto, Shunsuke
Highlights: Fracture initiation from interface free-edge of Si/Cu micro-components is experimentally evaluated. Strength of specimens having the same free-edge angle but different outer shape is expressed by a critical K. Strength of specimens having different free-edge angles is expressed by a unique critical K-lambda relation. The validity of the fracture mechanics criterion is successfully confirmed for micro-components. Abstract: Fracture initiation from an interface free-edge of bonded silicon (Si) and copper (Cu) micro-components is quantitatively studied in detail. By using three specimen types having the same free-edge angles (135°/135°) but different outer shape, the validity of the fracture mechanics criterion is firstly evaluated. It is shown that the fracture initiation strength represented by the elastic stress intensity factor (SIF) of the near-edge normal stress ( K θθ, C ) agrees irrespective of the specimen type. The effect of free-edge angle is then evaluated by different specimen types, i.e. 135°/135°, 120°/120° and 105°/105°. It is shown that, while the difference of free-edge angle leads to the different stress singularity λ, the near-edge normal stress distribution satisfies a unique relation, ( K θθ, λ)C, mediated by a specific point stress. This again indicates the validity of the generalized fracture mechanics criterion that involves both K and λ.